Gratitude and Social Media: A Pilot Experiment on the Benefits of Exposure to Others’ Grateful Interactions on Facebook - Sciara, Simona; Villani, Daniela; Di Natale, Anna Flavia; Regalia, Camillo (Frontiers in Psychology, 2021)
Facebook and other social networking sites allow observation of others’ interactions which in normal, offline life would simply be undetectable (e.g., a two-voice conversation viewable on the Facebook wall, from the perspective of a real, silent witness). Drawing on this specific property, the theory of social learning and the most direct implications of emotional contagion, our pilot experiment (N = 49) aimed to test whether the exposure to others’ grateful interactions on Facebook enhances (a) users’ felt gratitude, (b) expressed gratitude, and (c) their subjective well-being. For the threefold purpose, we created ad hoc Facebook groups in which the exposure to some accomplices’ exchange of grateful messages for two weeks was experimentally manipulated, and users’ felt/expressed gratitude and well-being consequently assessed. Results partially supported both hypotheses. Observing others’ exchange of grateful posts/comments on Facebook appeared to enhance participants’ in-person expression of gratitude (i.e., self-reported gratitude expression within face-to-face interactions), but not their direct and subjective experience of gratitude. Similarly, exposure to others’ grateful messages improved some components of subjective well-being, such as satisfaction with life, but not negative and positive affect. Taken together, however, our preliminary findings suggest for the first time that social networking sites may actually amplify the spreading of gratitude and its benefits. Implications of our results for professionals and future research in the field of health, education, and social media communication are discussed.